2017
DOI: 10.18405/recfin20170108
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Reactions on Returns and Trading Volume: The Impact of the Global Financial Crisis

Abstract: Objective: This study empirically examines the short term under-and overreaction effect in the Karachi Stock Exchange, Pakistan, in the context of the 2008 Global Financial Crisis considering the period from September 2007 to 2009. Background: Investors' probable reaction to an anticipated or unforeseen event is gaining immense importance in order to understand the complex market behavior. The arrival of good or bad news can tend to bring about a rise or decline in the stock price even if the news does not dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(45 reference statements)
2
1
0
Order By: Relevance
“…It is in accordance with the research hypothesis that there is an overreaction significant and inversely proportional relationship between trading volume and the overreaction phenomenon. These results are in line with the research by Ali, Ahmad and Anusakumar (2012) and Sohail, Rehman and Javid (2017) pointing out that stocks that have a smaller trading volume are increasingly prone to overreaction.…”
Section: Resultssupporting
confidence: 92%
“…It is in accordance with the research hypothesis that there is an overreaction significant and inversely proportional relationship between trading volume and the overreaction phenomenon. These results are in line with the research by Ali, Ahmad and Anusakumar (2012) and Sohail, Rehman and Javid (2017) pointing out that stocks that have a smaller trading volume are increasingly prone to overreaction.…”
Section: Resultssupporting
confidence: 92%
“…This means that the smaller the trading volume of shares at the time of the event compared to the trading volume of the previous day causes the stock to experience the phenomenon of overreaction easily. These results are consistent with the results of research conducted by Ali et al (2011) andSohail et al (2017) that stocks with a smaller trading volume are increasingly prone to overreaction.…”
Section: Cross-sectional Regression Testsupporting
confidence: 93%
“…Stock price, trading volume and KSE 100 index were obtained and the results showed that there is evidence of significant overreaction in the first two weeks and significant under-reaction in the 12th and 24th week in the financial sector. For the non-financial sector, the returns stayed positive and insignificant for both the winner and loser portfolios, thereby negating any evidence of significant overreaction [18].…”
Section: Empirical Reviewmentioning
confidence: 90%